Coronary heart disease incidence still decreased between 2006 and 2014 in France, except in young age groups: Results from the French MONICA registries. (1st July 2020) - Meirhaeghe, Aline; Montaye, Michèle; Biasch, Katia; Huo Yung Kai, Samantha; Moitry, Marie; Amouyel, Philippe; Ferrières, Jean; Dallongeville, Jean
Abstract : Background: Over the past few decades decreases in coronary heart disease morbidity and mortality rates have been observed throughout the western world. We sought to determine whether the acute coronary event rates had decreased between 2006 and 2014 among French adults, and whether there were sex and age-specific differences. Methods: We examined the French MONICA population-based registries monitoring the Lille urban area in northern France, the Bas-Rhin county in north-eastern France and the Haute Garonne county in south-western France. All acute coronary events among men and women aged 35–74 were collected. Results: Over the study period, the age-standardised attack rates decreased in both men (annual percentage change −1.5%, P  = 0.0006) and women (annual percentage change −2.1%, P  = 0.002). Also, the age-standardised incidence rates decreased in both men (annual percentage change −0.9%, P  = 0.03) and women (annual percentage change −1.8%, P  = 0.002) due to decreases in the 65–74 year age group. In men, age-standardised mortality rates decreased by 3.5% per year ( P  = 0.0004), especially in the 55–64 and 65–74 year age groups. In women, these rates decreased by 4.3% per year ( P  = 0.0009), particularly in the 35–44 and 65–74 year age groups. We also observed significant decreases in case fatality among both men (annual percentage change −1.7%, P  < 0.0001) and women (annual percentage change −1.9%, P  = 0.009). Conclusions: Downward trends in acute coronary event attack, incidence and mortality rates were observed between 2006 and 2014 in men and women. This effect was age dependent and was primarily due to decreases in the 65–74 year age group. There were no substantial declines in the younger age groups except for mortality in young women. Prevention measures still need to be strengthened, particularly in young adults.